Preparación de glutaraldehído 1,5 14C - Arciprete, C.P.; Mitta, A.E.A.; Correia, R.J. (Comisión Nacional de Energía Atómica (CNEA), 1972)
Fil:Arciprete, C.P. Comisión Nacional de Energía Atómica (CNEA). República Argentina